PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA PT TERMINAL TELUK LAMONG - TUS S, RACHMAWATI (Jurnal Ilmu Manajemen (JIM), 2017)
PT Terminal Teluk Lamong is a subsidiary of PT Pelabuhan Indonesia III (Persero). This company belongs to the new company, which was founded three years ago. The company is engaged in the service of the vessel, service items, service of dry bulk, container terminal and services that aim to foster the efficiency of the logistics for the sake of a brilliant future in the domestic and international level. This research aims to know and explain the influence of motivation on performance of employees with organizational commitment as intervening variable on the Gen Y employee at PT Terminal Teluk Lamong. This research is a type of causal research that uses a quantitative approach with a population of 131 people and sampling techniques using simple random sampling with a sample of 98 employees Gen Y. Data analysis techniques using the assistance software smartPLS. The results of this research show that a positive and significant effect of motivation on performance of employees. Motivation does not affect the commitment of the organization. Organizational commitment have no effect on performance of employees. Organizational commitment cannot be an intermediate variable to the variables of motivation with the performance of employees. Keywords: Generation Y, Work Motivation, Organizational Commitment, Employee Performance